(untitled) (International Journal of Engineering and Computer Science, 2015)
Streaming is mostly referred as a delivery system for media content or dynamic data. HTTP was not designed for data streaming. HTTP communications are stateless, and they take place over TCP/IP where there is no continuous connection between the ends. Usually, HTTP responses are buffered rather than streamed. HTTP 1.1 added supports for streaming through keep-alive header so data could be streamed. There are various HTTP streaming strategies-Progressive http streaming, HDS (HTTP dynamic streaming), HLS (HTTP live streaming), HSS (Http smooth streaming), DASH(Dynamic adaptive streaming over http and some others. HTTP streaming works by breaking the overall stream into a sequence of small HTTP-based file downloads, each download loading one short chunk of an overall potentially unbounded transport stream. My focus is on http streaming. In this paper, a review of various streaming strategies has been presented